INVESTIGATION OF THE EFFECTS OF KIGELIA AFRICANA (LAM.) BENTH. EXTRACTS ON TM3 LEYDIG CELLS - NELISIWE PRENATE MASUKU; SOGOLO LUCKY LEBELO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The study reports the effects of acetone, methanol, and aqueous Kigelia africana extracts on the TM3 Leydig cells. Methods: The total phenolic contents were determined using Folin–Ciocalteu’s method. Antioxidant activity was determined using 1,1-diphenyl-2- picrylhydrazyl assay and flavonoid content assessed using quercetin as standard. Cell viability and cytotoxicity were assessed. Results: Total phenolic and flavonoid contents of the extracts were analyzed. Acetone extracts showed highest total phenolic content (105±3.65 mg gallic acid equivalent [GAE]/g) followed by methanol extracts (10.64±0.32 mg GAE/g) and, last, the water extract with the total phenolic content of 4.27±0.65 mg GAE/g. The same trend was observed with total flavonoid content where results recorded for acetone, methanol, and water extracts were 3.63 ±0.20 mg/g quercetin equivalent (QE), 0.16±0.01 mg QE/g, and 0.01±0.00 mg QE/g, respectively. The three extracts showed lower IC50 values compared to ascorbic acid (0.143±0.05 mg/ml, 0.023±0.004 mg/l, and 0.043±0.03 mg/ml for acetone, methanol, and water extracts, respectively). At 0.5 mg/ml of acetone extract, there was an increase in the testosterone production compared to the control. Conclusion: The findings of this study showed that K. africana could be recommended for use in the treatment of male infertility.